Joint flexion/extension angle estimation using ultra-wideband (UWB) radios - Wong, Wee Leong (2015)
Joint flexion/extension angle measurement is known to be of clinical importance. It is essential for investigating complex gait disorders and monitoring of process in rehabilitation. Comparing with many other measuring methods such as mechanical, visual, audio, radar magnetic and inertial tracking, wearable Ultra Wideband (UWB) is the best candidate for human motion tracking due to its high ranging and positioning accuracy, low cost, less power consumption and robust performance in various environments. The system is also much smaller as compared with other existing approaches. The purpose of this report is to present a wearable system for estimating human elbow or knee joint flexion/extension angle using Ultra Wideband radios. UWB radio is an electromagnetic waveform formed by a sequence of very short pulses. A UWB transmitting antenna and a receiving antenna were placed on human elbow or knee adjacent segments. A Goniometer will be attached on human joint together with the UWB transceivers to ensure that the measurement could be conducted under same reference frame for comparison. The estimated distances were calculated between transmitter and receiver through the estimation of propagation delay, using Time of arrival (TOA) of the first arrival path. This method is the most common method to estimate the distance. The estimated distance was used to estimate the joint flexion/extension angle and also the static measurement of the adjacent segments length of the arm or legs by applying law of cosines. The performance of this wearable UWB based system was compared with the goniometer by simultaneously measuring elbow joint angle at three different moving speeds: slow, normal, fast. The experimental results demonstrate that the system has reasonable performance with a slightly increase in error as the speed increases. The system is capable of taking indoor and outdoor measurements. This system can also replace the goniometer system for rehabilitation. It is shown that the system has sufficient accuracy for clinical applications.